2000
DOI: 10.1063/1.126358
|View full text |Cite
|
Sign up to set email alerts
|

Selective enhancement of 1540 nm Er3+ emission centers in Er-implanted GaN by Mg codoping

Abstract: The ∼1540 nm I13/24 to I15/24 Er3+ photoluminescence (PL) and photoluminescence excitation (PLE) spectra of Er-implanted Mg-doped GaN reveal a selective enhancement of one of the nine different Er3+ centers observed previously in PL and PLE studies of Er-implanted undoped GaN. These Er3+ PL spectra are excited selectively by pump wavelengths that correspond to broadband, below-gap absorption bands associated with different Er3+ centers. In the Er-implanted, Mg-doped GaN, both the 1540 nm PL spectrum characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…Rare earth (RE) doped semiconductor materials have been extensively studied over the last decade due to their potential in light-emitting device applications [1][2][3]. Particularly an important effort research has been devoted to III-V semiconductors doped with rare earth.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth (RE) doped semiconductor materials have been extensively studied over the last decade due to their potential in light-emitting device applications [1][2][3]. Particularly an important effort research has been devoted to III-V semiconductors doped with rare earth.…”
Section: Introductionmentioning
confidence: 99%
“…However, application of site selective PL and PL excitation spectroscopy (PLE), which allow to excite separately particular emitting centers, has shown that in wurtzite GaN there is a single dominant Er center which involves about 99% of the emitting Er ions [8]. On the other hand, it has been found that the above-band-gap excitation for this center is inefficient and its emission intensity is comparable to that of several minor centers [7][8][9], which probably involve less than 1% of Er ions.In our previous work we were able to determine, using PLE and site-selective PL, the structure of Stark-split excited …”
mentioning
confidence: 98%
“…Erbium doping of wide band gap semiconductors is particularly interesting for possible application in optical communications and colour displays [3]. The photoluminescence (PL) properties as well as electroluminescence of GaN doped with Er was intensively studied by several research groups [4][5][6][7][8][9]. One of the remaining problems for applications is the identification of Er emitting centers.…”
mentioning
confidence: 99%
“…8 From PL and photoluminescence excitation different set of PL lines have been assigned to different Er site locations and/or Er-O ͑or other defects and impurities͒ related complexes. [2][3][4][5][6][7][8][10][11][12][13] Lines with full widths at half maximum ͑FWHM͒ larger than 1 meV are currently observed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] These are due to the intraionic transition of the Er 3ϩ between the two lowest spin-orbit levels 4 I 13/2 → 4 I 15/2 . Besides the well known infrared emission, visible luminescence from higher excited levels was also observed in molecular beam epitaxy ͑MBE͒ [8][9][10] and reactive sputtering 11 grown samples.…”
Section: Introductionmentioning
confidence: 99%